Roles of the RANKL–RANK Axis in Immunity—Implications for Pathogenesis and Treatment of Bone Metastasis - Li, Bo; Wang, Pengru; Jiao, Jian; Wei, Haifeng; Xu, Wei; Zhou, Pingting (Frontiers in Immunology, 2022)
A substantial amount patients with cancer will develop bone metastases, with 70% of metastatic prostate and breast cancer patients harboring bone metastasis. Despite advancements in systemic therapies for advanced cancer, survival remains poor for those with bone metastases. The interaction between bone cells and the immune system contributes to a better understanding of the role that immune system plays in the bone metastasis of cancer. The immune and bone systems share various molecules, including transcription factors, signaling molecules and membrane receptors, which can stimulate the differentiation and activation of bone‐resorbing osteoclasts. The process of cancer metastasis to bone, which deregulate bone turnover and result in bone loss and skeletal-related events (SREs), is also controlled by primary cancer-related factors that modulate the intratumoral microenvironment as well as cellular immune process. The nuclear factor kappa B ligand (RANKL) and receptor activator of nuclear factor kappa B (RANK) are key regulators of osteoclast development, bone metabolism, lymph node development and T-cell/Dendritic cell communication. RANKL is an osteoclastogenic cytokine that links bone and the immune system. In this review, we highlight the role of RANKL and RANK in immune microenvironment and bone metastases and review data on the role of the regulatory mechanism of immune in bone metastases, which could be verified through clinical efficacy of RANKL inhibitors for cancer patients with bone metastases. With the discovery of the specific role of RANK signaling in osteoclastogenesis, the humanized monoclonal antibody against RANKL, such as denosumab, was available to prevent bone loss, SREs and bone metastases, providing a unique opportunity to target RANKL/RANK as a future strategy to prevent bone metastases.